Hearing half the message? A re-audit of the care of patients with acute asthma by emergency ambulance crews in London. Issue 6 (2nd December 2005) - Snooks, H; Halter, M; Palmer, Y; Booth, H; Moore, F
Abstract : Problem: An initial audit of the care provided to emergency asthma patients by the ambulance service was carried out in 1996. Some under-recognition and under-treatment of severe asthma was found as well as a lack of documentation of patient condition on scene. A re-audit was undertaken in 1999. Design: A multidisciplinary advisory group was reconvened. The same method was adopted as for the first audit. Patients included were those administered nebulised salbutamol by crews in the catchment areas of four hospitals and those diagnosed with asthma at the Accident & Emergency (A&E) departments of those hospitals between January and March 1999. Setting: London Ambulance Service. Key measures for improvement: (1) Accuracy of diagnosis and appropriateness of treatment, and (2) adherence to protocol. Strategies for change: Following the first audit, treatment protocols were widened and brought into line with the British Thoracic Society guidelines for care of acute asthma patients. The results were widely disseminated within the service and training was initiated for all operational staff. Effects of change: The number of patients included in the re-audit more than doubled (audit 1: n = 252, audit 2: n = 532). The increase occurred exclusively in those administered nebulised salbutamol by ambulance crews but diagnosed with conditions other than asthma in A&E (audit 1: n = 15, audit 2: n = 161). The proportion of patients diagnosed with asthma in A&E who were administered nebulised salbutamol by their attending crew rose from 58% to 75%. However, 43 asthma patients were not treated; several of these were not recognised as suffering from asthma and others fell within the changed protocols for treatment. Adherence to protocol for administration of salbutamol remained high. Pre-hospital documentation of key observations did not improve. Lessons learnt: Messages from the first audit seem to have been acted upon selectively. Implementing change is complex, and re-audit is necessary to understand the effects of the changes made.